Persistent intraoperative sinus tachycardia: threat of thyroid storm? A case report - Deshmukh, Shubhada Rajendra; Pahuja, Heena; Palsodkar, Supriya; Jagtap, Rasika (International Journal of Research in Medical Sciences, 2017)
Sinus tachycardia in a patient undergoing surgery under general anaesthesia is not an uncommon experience in anaesthesia practice. Causes of intraoperative sinus tachycardia can be multi-factorial. Operative causes are pain, surgical stimulation and light depth of anaesthesia. Pharmacological factors include administration of catecholamines, atropine, or ketamine. Medical factors such as sepsis, hypovolaemia, heart failure, anaemia, and thyrotoxicosis should also be considered. We report a case of inadequately controlled hyperthyroidism undergoing surgery for a spinal cord tumour under general anaesthesia who developed unexplained tachycardia intraoperatively.